증강현실(AR) 영상인식 기술을 적용한 디지털 교과서 디자인 기획 -중학교 과학1 디지털 교과서 중심으로 - 유영미; 조성환; Yoo, Young-Mi; Jo, Seong-Hwan (한국콘텐츠학회 논문지, 18(6), 2018)
According to the Digi Capital forecast, the global augmented reality market is expected to grow rapidly by 2020 to reach 150 billion dollars. In particular, high value added effects are expected in education. As ICT advances, digital textbooks are also leading innovative education by adding interactive functions. Advanced countries, including the U.S., are already using digital textbooks that use augmented reality technology in their classes. In line with this technological outlook, the ministry proposed a design plan that applies augmented reality technology to middle school science 1 digital textbooks. A study on middle school science 1 digital textbooks showed that each unit provided short videos. In addition, an investigation into the augmented reality class case showed that it was difficult to establish experimental equipment, lack of equipment (devices), and 3D design contents that did not continue despite the excellence of learning effects. Based on this demand, we designed an augmented reality scenario and system configuration to be applied to the instrument-specific experiments of middle school science 1 digital textbooks to explore and explore the contents of augmented reality by students. This research will replace the dangerous experiments and time consuming experiments for teachers and students by applying augmented reality to science subjects that are essential for the development of digital textbooks. Digi-Capital 전망 자료에 따르면 전 세계 증강현실(AR) 시장 규모는 2020년까지 급성장해 1,500억 달러에 달할 것으로 예측하고 있다. 특히, 교육 분야에서 고부가가치 효과를 전망하고 있다. 정보통신 기술이 발전하면서 디지털 교과서 또한 인터랙티브한 기능이 추가되어 혁신적인 교육을 선도하고 있다. 이미 미국 등의 선진국에서는 디지털 교과서에 증강현실 기술을 적용한 디지털 교과서를 수업에서 활용하고 있다. 이런 기술적인 전망에 맞춰 중학교 과학1 디지털 교과서에 증강현실 기술을 적용한 디자인 기획 방향을 제안하였다. 현재 중학교 과학1 디지털 교과서를 조사한 결과 단원별 실험 과정이 짧은 동영상만을 제공하고 있었다. 또한 증강현실 수업 사례를 조사한 결과 학습 효과의 우수성에도 불구하고 지속적으로 이어지지 않은데는 실험 장비 구축의 어려움, 기자재(디바이스) 및 3D 디자인 콘텐츠 부족 등임을 알 수 있었다. 이런 요구를 종합하여 중학교 과학1 디지털 교과서의 단원별 실험 과정에 증강현실을 적용한 시나리오와 시스템 구성도를 설계하여 AR 아이콘을 통해 학생들 스스로 증강현실 3D 콘텐츠를 조작하고 탐구할 수 있도록 디자인 하였고 디자인한 모형 평가를 통해 학습 효과의 우수성을 제시하였다. 본 연구는 교육부의 디지털 교과서 개발에 있어 실험이 필수인 과학 과목에 증강현실을 적용한 디지털 교과서가 개발되어 교사와 학생들에게 위험한 실험, 시간 소요가 많은 실험 등을 대체할 수 있는 지속 가능한 효과적인 학습이 될 것으로 기대한다.